IFRS adoption and its impact on multinational entities - Kireeva, Kamilla (2023)
Implications of the IFRS transition in multinational companies – Empirical evidence from multinational companies The purpose of the future work is to study the theoretical foundations of the transition from national standards to international ones, the practice of applying several options for such a transition, consideration of the difficulties, differences and prospects for further accounting, as well as elucidating the effect of such a transition in terms of accounting indicators.